2020
DOI: 10.1096/fj.201903133rr
|View full text |Cite
|
Sign up to set email alerts
|

CHCHD10‐regulated OPA1‐mitofilin complex mediates TDP‐43‐induced mitochondrial phenotypes associated with frontotemporal dementia

Abstract: Mutations in CHCHD10, a gene coding for a mitochondrial protein, are implicated in ALS‐FTD spectrum disorders, which are pathologically characterized by transactive response DNA binding protein 43 kDa (TDP‐43) accumulation. While both TDP‐43 and CHCHD10 mutations drive mitochondrial pathogenesis, mechanisms underlying such phenotypes are unclear. Moreover, despite the disruption of the mitochondrial mitofilin protein complex at cristae junctions in patient fibroblasts bearing the CHCHD10S59L mutation, the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 67 publications
(220 reference statements)
3
54
0
Order By: Relevance
“…Given the limitations of the technology in that we could not control levels of transgene expression with exquisite precision, we proceeded with the best available lines. A recent report describes the development of a transgenic mouse model expressing FLAG-tagged CHCHD10 under the control of the CNS-enriched Prp promoter ( Liu et al., 2020a ). FLAG-tagged CHCHD10-R15L transgenic mice display one-half the transgene expression level of the FLAG-tagged CHCHD10-WT control mice, again highlighting the inherent difficulties of obtaining transgenic mice with comparable transgene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limitations of the technology in that we could not control levels of transgene expression with exquisite precision, we proceeded with the best available lines. A recent report describes the development of a transgenic mouse model expressing FLAG-tagged CHCHD10 under the control of the CNS-enriched Prp promoter ( Liu et al., 2020a ). FLAG-tagged CHCHD10-R15L transgenic mice display one-half the transgene expression level of the FLAG-tagged CHCHD10-WT control mice, again highlighting the inherent difficulties of obtaining transgenic mice with comparable transgene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in CHCHD10 have been found to be responsible for a large clinical spectrum including cardiomyopathy, ALS and/or FTD (Bannwarth et al , 2014; Liu et al , 2020; Johnson et al , 2014; Müller et al , 2014). It has been shown that CHCHD10 forms large aggregates with the paralog CHCHD2 protein in the affected tissues and it is very likely that CHCHD10/CHCHD2 aggregation is involved in the pathological process (Anderson et al , 2019; Huang et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SLP2 and the PHB complex are thus necessary to control the activity of OMA1 and the processing of OPA1. CHCHD2 variants, involved in Parkinson’s disease (PD), and CHCHD10 mutations lead to OMA1 activation when overexpressed in human cells (Liu et al , 2020). Here, we show that CHCHD10 is required with SLP2 for the maintenance of the PHB complex and that, in our models, OMA1 activation is triggered by the destabilization of this complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations